Large-Scale Land Acquisitions - Gironde, C.; Golay, C.; Messerli, P. (Brill, 2015)
This book examines large-scale land acquisitions, or
English
Keywords: Development studies; international development; Cambodia; Human rights; Laos; Natural rubber; Sugarcane